2020
DOI: 10.1084/jem.20191206
|View full text |Cite
|
Sign up to set email alerts
|

Membrane budding is a major mechanism of in vivo platelet biogenesis

Abstract: How platelets are produced by megakaryocytes in vivo remains controversial despite more than a century of investigation. Megakaryocytes readily produce proplatelet structures in vitro; however, visualization of platelet release from proplatelets in vivo has remained elusive. We show that within the native prenatal and adult environments, the frequency and rate of proplatelet formation is incompatible with the physiological demands of platelet replacement. We resolve this inconsistency by performing in-depth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 69 publications
(106 reference statements)
4
55
0
Order By: Relevance
“…However, under special conditions associated with strongly increased platelet turnover, platelets can be released through megakaryocyte rupture [ 7 ]. More recently, based on the calculation of the rate of proplatelet formation required for physiological platelet replacement, it has been suggested that membrane budding, rather than proplatelet formation, supplies the majority of the platelet biomass in vivo [ 8 ]. The release of platelets in lungs by megakaryocytes entered in blood and disintegrated by the impact with the pulmonary microcirculation has also been shown, but its relevance for platelet production is a matter of controversy [ 9 ].…”
Section: Megakaryocytopoiesis and Platelet Productionmentioning
confidence: 99%
“…However, under special conditions associated with strongly increased platelet turnover, platelets can be released through megakaryocyte rupture [ 7 ]. More recently, based on the calculation of the rate of proplatelet formation required for physiological platelet replacement, it has been suggested that membrane budding, rather than proplatelet formation, supplies the majority of the platelet biomass in vivo [ 8 ]. The release of platelets in lungs by megakaryocytes entered in blood and disintegrated by the impact with the pulmonary microcirculation has also been shown, but its relevance for platelet production is a matter of controversy [ 9 ].…”
Section: Megakaryocytopoiesis and Platelet Productionmentioning
confidence: 99%
“…Megakaryocytes are thought to produce platelets via a cytoskeletal-driven process, in which cytoplasmic protrusions called proplatelets extend from the BM and into the blood stream 3 , 4 . However, this model for platelet synthesis was recently challenged, because megakaryocyte membrane budding, rather than proplatelet formation, was reported to supply the majority of the platelet biomass 5 . Alternative mechanisms, such as megakaryocyte rupture, have been proposed in response to acute needs 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 18 A recent study demonstrated that membrane budding also contributes to supply the platelet biomass. 19 For erythrocytes the crucial step entails expulsion of the nucleus from erythroblasts, which leads to the formation of reticulocytes, and the loss of organelles and ribosomes through autophagy/exosome-combined pathways. 20 …”
Section: Looking Inside the Bone Marrow: An Overview On The Origin Of Blood Platelets And Erythrocytes In Vivomentioning
confidence: 99%